SERAPAN NITROGEN BIBIT ROTAN PADA PERLAKUAN PUPUK ORGANIK DAN ANORGANIK - Lisa Indriani Bangkele (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
Indonesia as the world's major producer and supplier of rattan, but most of Indonesia's rattan production relies on natural rattan sources. The fact that natural rattan is generally harvested after the age of more than 4 years, is not proportional to harvesting at any time, and threatens the preservation of rattan, so research on rattan cultivation is important. This study focuses on the growth and absorption of Noko rattan seedlings varieties (Daemonorops sp.) in response of organic and inorganic fertilization. Research was conducted in the glass house of UNTAD, using factorial design of 2 (two) factors. Factor I consists of 2 (two) levels, namely: (B0) without bokashi, and (B1) bokashi 10 t / Ha. Factor II consists of 7 (seven) variations of Nitrogen and Phosphorus treatments. The results showed that the treatment of organic fertilizer and inorganic fertilizer had no significant effect on dry weight or nitrogen uptake (N) or N network. However treatment with bokashi showed a tendency of dry weight and alsoN uptake or N tissue higher than treatment without bokashi. In this study, treatment with bokashi added Urea fertilizer gives the best influence on the growth of Noko rattan seedlings.